Caracterização tecnológica de minério fosfático de Salitre-Patrocínio -MG - Luiz Antonio Fonseca de Barros (2006)
This investigation describes the technological characterization of the phosphate ore from Salitres Alkaline-Carbonatite Complex, located in the west of Minas Gerais state, near the town of Patrocinio. The characterization of Salitres phosphate ore was performed with the help of a basic conceptual methodology of technological characterization. It is worthwhile stressing the relevance of the technological characterization for the mining explotation in all its aspects: technical, economic and industrial. The results presented show the variability and differences in the technological behavior among the ore types in Salitres reserve. Such variability is observed in the morphological types of apatite and in the unit operations of mineral processing, especially froth flotation. This study aimed at identifying the critical parameters related to the concentration of apatite. Based on these studies it was possible to realize the importance of ore types on the process responses and thus on expected industrial results. Next to exploratory experiments, a deeper technological characterization of each ore type was performed, involving fundamental studies, searching for the basic reasons of process problems, as well as the causes that might represent advantages or gains in the industrial processing. The goal was collecting a broader range of pieces of information, aiming at ore blendings more adequate for the concentration process, resulting in enhanced phosphorus recovery and reduction in industrial costs. The search for technical indicators characteristic of apatites, mineralogical guides associated with standard flotation tests provided a deeper and more reliable technical analysis as the easiest route for planning the utilization of the ore reserve. The results of the technological characterization performed on the different ore typesfrom Salitres deposit rendered feasible a technical and economical plan to establish the.